Interpretação de pronomes e aquisição de dependências referenciais em português L2 - Fiéis Alexandra; Madeira, Ana (Revista da Associação Portuguesa de Linguística, 2016)
This study investigates whether L2 learners of (European) Portuguese display asymmetries in their comprehension of reflexive and non-reflexive pronouns, as has been found in L2 English (e.g., Kim, Montrul & Yoon, 2014). Forty- one intermediate learners of L2 Portuguese, who were L1 speakers of Spanish, English and Chinese, completed a truth-value judgement task (Silva, 2015) testing both reflexive and non-reflexive object clitics. The three groups achieved targetlike results in their interpretation of both types of pronouns. These findings indicate that, unlike strong pronouns, clitic pronouns pose no difficulties for learners, which suggests that, as previously shown for L1 acquisition (e.g., McKee, 1992), the grammatical status of pronouns (strong vs. clitic) is also relevant in L2 acquisition.